PEMAHAMAN KESETARAAN GENDER ANGGOTA KOPWAN BAMBU KUNING (ANALISIS PERSPEKTIF GENDER) - Ernaningsih Ernaningsih (PENTAS : Pendidikan Bahasa dan Sastra Indonesia, 2021)
This paper tries to reveal the understanding of the mothers of KOPWAN Bambu Kuning members about equality, in the form of understanding of mothers in the form of: gender stereotypes, discriminatory roles, workload and Violence or gender violence. This research, which was conducted on a number of women members of KOPWAN Bambu Kuning, used a descriptive qualitative method with a gender perspective approach. The data in this study are data about: gender stereotypes, discriminatory roles, workload and Subordination. Sources of data obtained from documentation and informants. The data collection technique is done by documentation and interviews. The data analysis technique uses an interactive technique using the Miles Huberman model. The research findings can describe: views on gender stereotypes, discriminatory roles experienced by mothers reflecting gender relations, workload caused by gender relations and, violence caused by gender relations.